1996
DOI: 10.1242/jcs.109.7.1813
|View full text |Cite
|
Sign up to set email alerts
|

A biochemical and immunological comparison of nuclear and cytoplasmic pore complexes

Abstract: Pore complexes are not confined to the nuclear envelope but can also be found in the cytoplasm of numerous cell types in the form of annulate lamellae (AL). We have induced formation of AL by exposure of rat cells (line RV) to sublethal doses of the antimitotic drug vinblastine sulfate, and compared the distribution of several nuclear pore complex proteins (nucleoporins) in the nuclear envelope and AL by immunocytochemistry, cytochemical lectin binding studies and immunoblot analyses of nuclear and AL-enriched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Indeed, addition of nocodazole, colcemid, as well as AS-2 (inhibitor of kinesin-mediated microtubule-dependent transport) did not prevent the formation of the nuclear envelope, but nuclei formed under these conditions lacked nuclear pore complexes and were therefore unable to accumulate karyophilic proteins. It is interesting to note that the assembly of annulate lamellae, a cytoplasmic structure forming stacks of membranes containing pore complexes similar to those of nuclear envelope but different in protein composition (studied in more details in mammalian cells [106,107]), was not affected by these same perturbations [105]. In addition, by combining Xenopus egg extracts with microfluidic devices to control the space occupied by microtubules around nuclei, Hara and Merten showed that dynein-based accumulation of membranes regulates nuclear expansion [27].…”
Section: The Control Of Nuclear Assembly and Disassembly By The Microtubule Cytoskeletonmentioning
confidence: 99%
“…Indeed, addition of nocodazole, colcemid, as well as AS-2 (inhibitor of kinesin-mediated microtubule-dependent transport) did not prevent the formation of the nuclear envelope, but nuclei formed under these conditions lacked nuclear pore complexes and were therefore unable to accumulate karyophilic proteins. It is interesting to note that the assembly of annulate lamellae, a cytoplasmic structure forming stacks of membranes containing pore complexes similar to those of nuclear envelope but different in protein composition (studied in more details in mammalian cells [106,107]), was not affected by these same perturbations [105]. In addition, by combining Xenopus egg extracts with microfluidic devices to control the space occupied by microtubules around nuclei, Hara and Merten showed that dynein-based accumulation of membranes regulates nuclear expansion [27].…”
Section: The Control Of Nuclear Assembly and Disassembly By The Microtubule Cytoskeletonmentioning
confidence: 99%